Main Differences of DevOps on IoT Systems - Pereira, Igor; Carneiro, Tiago; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
IoT systems have barriers related to the different areas that involve their development. Hence, the scientific literature and industry practices investigate approaches that enable continuous interaction of these areas. Through semi-structured interviews with thirty-one professionals working in industry, this study investigated how DevOps is applied to make the development of IoT projects continuous and meet the demands of the industry. Through group discussions, we categorized the results of this study. As a preliminary contribution to this work, we investigate the contrasts between using DevOps in IoT system projects and using rigid, plan-oriented processes to develop embedded systems.